The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/boj.12058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative systematic study of colleters and stipules of Rhizophoraceae with implications for adaptation to challenging environments

Abstract: Colleters are multicellular secretory structures found on various organs in flowering plants. Colleters on the adaxial sides of stipules have been hypothesized to play a role in protecting the developing shoot. Rhizophoraceae is a stipulate family with a broad distribution from mangrove to montane environments, which makes the family well suited for the examination of this hypothesis, but the colleters of Rhizophoraceae are not well known. We compared species from all three tribes of Rhizophoraceae, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The occurrence of druses in the parenchyma of the colleter central axis in all studied species is a character with potential taxonomic value within Euphorbiaceae or even in Malpighiales. In fact, within the other families in this order, druses have been reported in the core parenchyma region of colleters in Rhizophoraceae (Sheue et al, 2012, 2013), whereas they are absent in the colleters of Caryocar brasiliense Cambess. in the Caryocaraceae (Paiva and Machado, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…The occurrence of druses in the parenchyma of the colleter central axis in all studied species is a character with potential taxonomic value within Euphorbiaceae or even in Malpighiales. In fact, within the other families in this order, druses have been reported in the core parenchyma region of colleters in Rhizophoraceae (Sheue et al, 2012, 2013), whereas they are absent in the colleters of Caryocar brasiliense Cambess. in the Caryocaraceae (Paiva and Machado, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Although some colleter characteristics (e.g. morphology, number and distribution) may be phylogenetically determined (Sheue et al 2012(Sheue et al , 2013, some studies have reported changes in colleters' functional performance traits associated with environment, which suggests that there is an ecological constraint related to the role of secretion in natural conditions (Sheue et al 2012(Sheue et al , 2013Tresmondi et al 2015). By comparing members of Rubiaceae growing in contrasting vegetation types (forest and savanna), we found that colleters similar in morphology and anatomical organisation differ in the chemical composition of secretions (Tresmondi et al 2015).…”
Section: Communicated By: Sven Thatjementioning
confidence: 99%
“…We are aware of other potentially diagnostic characters, like the colleters at the base of the conspicuous interpetiolar stipules of this genus (Hou, 1958;Sheue et al, 2013). However, for this assessment, we have relied on morphological characters known to be diagnostic for comparable taxa within this genus worldwide (Duke & Ge, 2011;Cooper et al, 2016;Duke & Kudo, 2018) Reports until now revealed the existence of a hybrid intermediate only in countries in the eastern portion of the parental overlap zone in both northern and southern hemispheres like southern China, Malesia, Papua New Guinea and northern Australia (Duke & Ge, 2011;Muhamad et al, 2016;Tomlinson, 2016;Duke, 2017).…”
Section: Bruguieramentioning
confidence: 99%